Adverse Reaction of Acupuncture and Antihypertensive Drugs for Treatment of Essential hypertension: A Protocol for Bayesian Network Meta-Analysis. (21st August 2022) - Han, Jiawei; Yang, Jiwei; Du, Yuanhao
Abstract : Background . Hypertension, as a high risk factor of cardiovascular disease, has led to a significant upward trend in the population and incidence of the disease. Hypertension patients need to take antihypertensive drugs for life, and therefore people gradually pay more attention to the adverse reactions of antihypertensive drugs. This study protocol outlines a plan to assess the adverse reaction of the different antihypertensive drugs and acupuncture in order for clinical application. Objective . To compare the side effects of different antihypertensive drugs and acupuncture in the treatment of hypertension. Methods and analysis. We will search the databases containing CNKI, Wan-Fang database, Chinese Scientific Journal Database(VIP), PubMed, Cochrane, and Embase, and randomized controlled trials (RCTs) of commonly used antihypertensive drugs or acupuncture for primary hypertension will be obtained. Then, Stata14.0 and Gemtc will be used to assess the statistics. Ethics and dissemination . Since no personal patient consent will be required in the study, there is no ethical approval. The results of this reporting will be submitted to a peer-reviewed publication. PROSPERO registration number: CRD42020152703.